Social representations of Covid-19 and stigmatization of healthcare personnel and people attained by abidjanese populations, Cote d’Ivoire - Kouame Kouakou Félicien,; Digbeu Alain Fabrice,; Samouth Aka Fabrice, (Technium Social Sciences Journal, 2020)
The present study aims to identify the structure of coronavirus social representations in order to understand the stigmatization of people with Covid-19 and of healthcare personnel by populations in Abidjan. To do this, we have drawn up a sample made up of the unemployed, pupils and students and workers. There are 325 participants, including 177 men and 148 women, with an age that varies between 16 and 59 years. These people are subjected to the evocation questionnaire according to the structural approach of social representations (Abric, 1994). Analysis of the data using evoc2005 and simi2005 shows that the evocations "containment", "death" and "invention" constitute the main components (central core) of the social representations of coronavirus. These elements, which reflect a lived experience of negative feelings, will generate the construction of negative prejudices and common beliefs that encourage avoidance behaviours among participants to flee the feared situation. It takes place inward withdrawal and rejection of the other which constitutes for the individual a danger. Hence the stigmatization of people who visibly "embody" danger, death (the object of fear), namely people with Covid-19 and caregivers. The results therefore suggest that in the fight against Covid-19 the psychological aspect is also important and must be taken into account.